Prospective study on prevalence, intensity, type, and therapy of acute pain in a second-level urban emergency department - Mura P; Serra E; Marinangeli F; Patti S; Musu M; Piras I; Massidda MV; Pia G; Evangelista M; Finco G (Journal of Pain Research, 2017)
Paolo Mura,1 Elisabetta Serra,1 Franco Marinangeli,2 Sebastiano Patti,3 Mario Musu,1 Ilenia Piras,3 Maria Valeria Massidda,1 Giorgio Pia,3 Maurizio Evangelista,4 Gabriele Finco1 1Department of Medical Sciences “M. Aresu”, University of Cagliari, Cagliari, Italy; 2Department of Anesthesiology, Intensive Care and Pain Medicine, University of L’Aquila, L’Aquila, Italy; 3Department of Emergency Medicine, Santissima Trinità Hospital, Cagliari, Italy; 4Department of Anesthesiology and Pain Medicine, Cattolica University, Rome, Italy Aim: Pain represents the most frequent cause for patient admission to emergency departments (EDs). Oligoanalgesia is a common problem in this field. The aims of this study were to assess prevalence and intensity of pain in patients who visited a second-level urban ED and to evaluate the efficacy of pharmacological treatment administered subsequent to variations in pain intensity. Methods: A 4-week prospective observational study was carried out on 2,838 patients who visited a second-level urban ED. Pain intensity was evaluated using the Numeric Rating Scale at the moment of triage. The efficacy of prescribed analgesic therapy was evaluated at 30 and 60 minutes, and at discharge. Data concerning pain intensity were classified as absent, slight, mild, or severe. Pain was evaluated in relation to the prescribed therapy. Results: Pain prevalence was 70.7%. Traumatic events were the primary cause in most cases (40.44%), followed by pain linked to urologic problems (13.52%), abdominal pain (13.39%), and nontraumatic musculoskeletal pain (7.10%). Only 32.46% of patients were given pharmacological therapy. Of these, 76% reported severe pain, 19% moderate, and 5% slight, and 66% received nonsteroidal anti-inflammatory drugs or paracetamol, 4% opioids, and 30% other therapies. A difference of at least 2 points on the Numerical Rating Scale was observed in 84% of patients on reevaluation following initial analgesic therapy. Conclusion: Pain represents one of the primary reasons for visits to EDs. Although a notable reduction in pain intensity has been highlighted in patients who received painkillers, results show that inadequate treatment of pain in ED continues to be a problem. Keywords: pain, emergency department, oligoanalgesia, pain treatment, pain assessment, NSAIDs, opioids, methoxyflurane, traumatic pain, abdominal pain